KARAKTERISTIK SIFAT FISIKOKIMIA NATA DE TARO TALAS BENENG DENGAN PERBEDAAN KONSENTRASI ACETOBACTER XYLINUM DAN SUMBER KARBON - Tuti Rostianti Maulani, Dini Nur Hakiki dan Nursuciyoni (Jurnal Teknologi Industri Pertanian, 2018)
The aim of this research was to characterize nata de taro from Talas Beneng (Xanthosoma undipes K. Koch) with different concentrations of Acetobacter xylinum and carbon source.Grated talas beneng was added 1 liters of water and settled for 24 hours until separated water and starch. The water was boiled, added 5% sucrose, 2% acetat acid, 1% urea, cooled to 25oC than added concentration of Acetobacter xylinum with different level 10%, 15%, 20%, and 25%. Nata formed on day 13 then analyzed yield, weight, hardness, organoleptic, crude fiber. The study of carbon source used A. xylinum concentration of 15% with each 5% of sucrose, glucose, and fructose than analyzed yield, thickness, dan crude fiber. The results showed that addition A. xylinum had effect characteristic of nata de taro. The higher concentration of A. xylinum tends to produce higher yield, thickness and organoleptic especially and texture and flavour. The addition of 25% concentration of A. xylinum was the highest yield and thickness as 30.98%, and 9.55 mm, then it has crude fiber 4.89% and hardness 0.1 mm/g.s, and organoleptic between 3.05-3,27 (enough preferred). The addition of source of carbon from sucrose was the higheryield and thickness than glucose and fructose as 41,6%, 0.90 cm.Keywords:Acetobacter xylinum, Nata, Talas Beneng